Childhood Misfortune and Adult Health: Enduring and Cascadic Effects on Somatic and Psychological Symptoms?. (February 2013) - Schafer, Markus H.; Ferraro, Kenneth F.
Objective: This article traces the influence of early misfortune on somatic and psychological symptoms, examining whether the health disadvantages endure and/or worsen over a decade.Method: The study uses two waves of data from the Midlife Development in the United States study. Structural equation models are used to assess change in somatic and psychological symptoms.Results: Findings reveal that childhood abuse is associated with more initial somatic and psychological symptoms among American adults, but that family structure and financial strain had little association with baseline adult symptoms. The effects of abuse were not observed at Wave 2 (W2), net of Wave 1 (W1) symptoms.Discussion: The results suggest an enduring—but not cascadic—effect of childhood abuse on adult health. There was little evidence that the consequences of early misfortune waned over the course of time or were less substantial for older adults; but neither did these early life experiences contribute to worsened symptoms over a decade of observation.